# Wilson's theorem proofing questions?

• May 8th 2012, 01:27 PM
Laban
Wilson's theorem proofing questions?
I've been asked to prove these 2 things :

1. $\displaystyle (-1)^{\frac{n-1}{2}}(1\cdot2\cdot\cdot\cdot(\frac{n-1}{2}))^{2} = -1$

2. if $\displaystyle n\equiv1 (mod 4)$ then x2=-1 has a solution.

I haven't manage to come by enough examples of Wilson's theorem, so I'm really in the dark here.
Any help will be much appreciated.

Thanks.
• May 8th 2012, 06:18 PM
wsldam
Re: Wilson's theorem proofing questions?
I will prove when 'n' is an odd prime (so we can invoke Wilson's Theorem).

Let p be an odd prime. Then by Wilson's Theorem:

$\displaystyle -1 \equiv (p-1)! mod p$
$\displaystyle -1 \equiv 1 \cdot 2 \cdot ... \cdot \frac{p-1}{2} \cdot \frac{p+1}{2} \cdot ... \cdot (p-1) mod p$
Since $\displaystyle p \equiv 0 mod p$ we can freely subtract p from each term in the second half of the previous equation. This gives us:
$\displaystyle -1 \equiv 1 \cdot 2 \cdot ... \cdot \frac{p-1}{2} \cdot (-\frac{p-1}{2} \cdot ... \cdot (-1)) mod p$
Now note that in the second half of the right hand side there are $\displaystyle \frac{p-1}{2}$ '-1's' (pardon my notation abuse). Pulling out the '-1's' we have the result.

If $\displaystyle p \equiv 1 mod 4$ then $\displaystyle \frac{p-1}{2} \equiv 0 mod 2$. Hence, by our previous result, $\displaystyle -1 \equiv [(\frac{p-1}{2})!]^2 mod p$. Therefore $\displaystyle x^2 \equiv -1 mod p$ has a solution.
• May 8th 2012, 08:20 PM
princeps
Re: Wilson's theorem proofing questions?
• May 9th 2012, 03:41 PM
Laban
Re: Wilson's theorem proofing questions?
Quote:

Originally Posted by wsldam
I will prove when 'n' is an odd prime (so we can invoke Wilson's Theorem).

Let p be an odd prime. Then by Wilson's Theorem:

$\displaystyle -1 \equiv (p-1)! mod p$
$\displaystyle -1 \equiv 1 \cdot 2 \cdot ... \cdot \frac{p-1}{2} \cdot \frac{p+1}{2} \cdot ... \cdot (p-1) mod p$
Since $\displaystyle p \equiv 0 mod p$ we can freely subtract p from each term in the second half of the previous equation. This gives us:
$\displaystyle -1 \equiv 1 \cdot 2 \cdot ... \cdot \frac{p-1}{2} \cdot (-\frac{p-1}{2} \cdot ... \cdot (-1)) mod p$
Now note that in the second half of the right hand side there are $\displaystyle \frac{p-1}{2}$ '-1's' (pardon my notation abuse). Pulling out the '-1's' we have the result.

If $\displaystyle p \equiv 1 mod 4$ then $\displaystyle \frac{p-1}{2} \equiv 0 mod 2$. Hence, by our previous result, $\displaystyle -1 \equiv [(\frac{p-1}{2})!]^2 mod p$. Therefore $\displaystyle x^2 \equiv -1 mod p$ has a solution.

Thanks a lot! I would have never figured it out on my own. I'm still baffled as to why we're getting these questions in a linear algebra course.